Diagnostic accuracy of toluidine blue in early detection of oral squamous cell carcinoma - Chishty, Muhammad Salman; Sajid, Malik Ali Hassan; Younus, Shoaib -; Haq, Usman Ul (Journal of Fatima Jinnah Medical University, 2021)
Background: Indian sub-continent (India, Pakistan, and Bangladesh) is one of the high-risk populations for oral cancer cases. Intraoral screening is critical to diagnosis and treating oral cancer at an early stage for a better prognosis. Among the diagnostic adjuncts, toluidine blue staining is considered a simplistic, cost-effective, and highly sensitive method. The objective of the current study was to find out the diagnostic accuracy of toluidine blue in the early detection of oral squamous cell carcinoma. Patients and methods: This prospective observational study was undertaken at the Department of Oral and Maxillofacial Surgery, Institute of Dentistry, CMH Lahore Medical College from15-09-2019 to 15-03-2020 after getting approval from IRB. Based on inclusion criteria, a sample size of 100 was calculated and enrolled in the study. Non-probability convenient sampling technique was utilized. Oral staining of 100 patients was done with 1% toluidine blue on an OPD basis, and incisional biopsies were then performed. Staining pattern and histopathology reports of patients were evaluated to assess the diagnostic accuracy Results: The study results revealed the sensitivity of Toluidine Blue as 89.87%, and specificity of toluidine blue was found as 76.19%. Positive and negative predictive values of Toluidine Blue remained 93.42% and 66.67%, respectively. Conclusion: Toluidine blue has good diagnostic accuracy for early detection of oral squamous cell carcinoma (SCC).